2020
DOI: 10.1097/md.0000000000018809
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of the association between the copy numbers of survival motor neuron gene 2 and neuronal apoptosis inhibitory protein genes and the clinical phenotypes in 40 patients with spinal muscular atrophy

Abstract: In this article, the correlation between the copy number of survival motor neuron 2 (SMN2) gene, neuronal apoptosis inhibitory protein (NAIP), and the phenotype of spinal muscular atrophy patients were analyzed.Forty patients with spinal muscular atrophy (SMA) were included in the study at the Department of Medical Genetics of the First People's Hospital and the Department of Neurology of the Second People's Hospital in Yunnan Province from January 2012 to September 2018. Multiplex ligation-dependent probe amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 34 publications
3
17
0
4
Order By: Relevance
“…This model only differs from Calucho's correlations in type III patients, since it establishes the expected SMN2_CN to be 4 instead of 3 and 4 indistinctly [9]. In the recent literature, the correlation described by Calucho et al (2018) is mainly maintained [28][29][30][31][32], although some exceptions can be found. Interestingly, the proportion of type I patients with 3 SMN2 genes was increased in some cohorts, reaching 57% among SMA I patients, while Calucho's compilation reported only 23% [33,34].…”
Section: The Known Validated Genotypesmentioning
confidence: 66%
“…This model only differs from Calucho's correlations in type III patients, since it establishes the expected SMN2_CN to be 4 instead of 3 and 4 indistinctly [9]. In the recent literature, the correlation described by Calucho et al (2018) is mainly maintained [28][29][30][31][32], although some exceptions can be found. Interestingly, the proportion of type I patients with 3 SMN2 genes was increased in some cohorts, reaching 57% among SMA I patients, while Calucho's compilation reported only 23% [33,34].…”
Section: The Known Validated Genotypesmentioning
confidence: 66%
“…But its role in pathogenesis has not been fully clear up yet (Ahn, Eun-ji, Yum, Mi-Sun 2016). In 2020, it was studied in 40 SMA patients in Yunnan Province, China, and it was demonstrated synergistic modi cation effects of the SMN2 and NAIP genes on the SMA phenotype (Zhang et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…SMA Type 4 occurs in the 20s or 30s and is the adult form of SMA. Compared to other types, the symptoms are milder, and SMA type 4 form is rarely seen (Zhang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent to previous studies, low SMN2 copies were strongly correlated with higher severity in patients with homozygous SMN1 deletions ( r = 0.78) [ 7, 12, 14, 19 ]. The secondary influence of low NAIP copies on the severity is also discussed in several studies; however data on the relative impact on the age of onset is not so well established) [ 20, 21 ]. With our study a statistically significant effect of NAIP gene copies was demonstrated when 0–1 copies were considered low, adjusted for SMN2 copies and gender.…”
Section: Discussionmentioning
confidence: 99%